Problematika Pangan Pada Pengemudi Ojek Online di Kawasan Tangerang Selatan - Wirawan, Raihan; Silvi Apri; Limbirth, Mikayla; Wulus, Aurellia Tiffany; Trixie, Pia; Jaha, Diandra Berlian; Raffasya, Muhammad Fadhl; Nicholas, Jack; Anthonius, Ferdy; Tambunan, Daulat Marulitua (Widya Duta: Jurnal Ilmiah Ilmu Sosial Budaya, 2025)
Social inequality in South Tangerang is one of the main challenges in sustainable development, especially for informal sector workers such as online motorcycle taxi drivers. This research aims to analyze the food access problems faced by online motorcycle taxi drivers in the region, identify the factors that influence them, and explore policy solutions that can improve their welfare. The research method used was descriptive qualitative, with data collection through short semi-structured interviews with 20 online motorcycle taxi drivers at the Pondok Ranji shelter, South Tangerang. The research results show that income instability, high costs of living, and limited access to nutritious food are the main obstacles for online motorcycle taxi drivers in meeting their basic needs. This study also highlights the important role of the government and ride-hailing companies in providing solutions such as food subsidies, price regulations for basic commodities, and more inclusive social assistance programs. These findings contribute to supporting the achievement of Sustainable Development Goals (SDGs) no. 2 regarding eliminating hunger and improving the welfare of informal workers in urban areas.